Carpal tunnel syndrome: A rare manifestation of distal radius osteoid osteoma - Basran, Sukhvinder Singh (J Clin Orthop Trauma, 2015)
Osteoid Osteoma is a benign bone tumor that normally affects long bones and rarely affects distal radius. Because of its nonspecific presentation in the wrist, it remains a diagnostic challenge. We report an unusual case of Osteoid Osteoma at distal radius having symptoms resembling that of carpal tunnel syndrome. The diagnosis was confirmed preoperatively with X-rays; bone scintigraphy, CT, and MRI, later histological examination confirmed the diagnoses. Surgical excision lead to a dramatic improvement in the condition of the patient.